The Effect of Speed Training on The Results of The Long Jump in Class X IPS Students of SMAN 1 OKU - DN, Asry Romadoni; Manullang, Jujur Gunawan; Putri, Siti Ayu Risma (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine how much influence speed training has on increasing long jump results in class X IPS students at SMA N 1 OKU. This research is experimental research using a pretest-posttest control group design with the independent variable speed training, the dependent variable the long jump result. The subjects in this study were male students of class X IPS students who were selected by the sampling technique, to determine the experimental and control groups the researcher used a simple random sampling technique with an ordinal pairing system. The data collection method used is a test. In each group, the test was given at the beginning before treatment and at the end after being given treatment. The treatment in the experimental group was in the form of speed training (30-meter sprint), After being given treatment for 5 weeks with a frequency of exercise 4 times a week. Based on data analysis by means of the t-test statistic with a significant level α = 0.05, it is obtained t count = 16.42 and t table = 1.771, if t-count > t-table then Ha is accepted and Ho is rejected. Thus, the truth that was proposed by Ha can be accepted, that speed training has an effect on long jump results in class X students at SMA N 1 Ogan Komering Ulu.